Bio Art: From Genesis to Natural History of Enigma - Kac, Eduardo; Sułkowska-Janowska, Mariola (Folia Philosophica, 2010)
The article deals with phenomenon of art which uses so-called wet or biological media. Eduardo Kac - the author of the article as well as of presented works - tries to introduce totally new form of art: bio art and some of its variants (transgenic art, telerobotic art, protein art or biotelematic art). At the same time he underlines philosophical, ethical and social implications of such artistic creation. Since his work explores the boundaries between humans, animals and robots, and moreover - it manipulates or even creates life, it must be pursued with great care, with acknowledgment of the complex issues it raises and, above all, with a commitment to respect, nurture and love the life created.